NOx depolluting performance of photocatalytic materials in an urban area - Part II: Assessment through Computational Fluid Dynamics simulations. (1st February 2021) - Sanchez, Beatriz; Santiago, Jose Luis; Martilli, Alberto; Palacios, Magdalena; Núñez, Lourdes; Pujadas, Manuel; Fernández-Pampillón, Jaime
Abstract: Photocatalytic materials are proposed as a mitigation strategy of urban air pollution because of its deposition feature. This study aims at evaluating their effect on NO2 concentrations in an urban environment under real atmospheric conditions through Computational Fluid Dynamics (CFD) simulations. A comprehensive study is performed to determine the potential of photocatalytic materials to remove NO2 at pedestrian level taking into account the variability of wind speed, traffic emissions and the photoactive area in an urban environment. The deposition velocity used to model the sink effect of a photoactive surface is derived from laboratory data and its applicability to outdoor conditions is proved through microscale simulations. The CFD simulation performed to assess the impact of a photocatalytic material on ambient pollutants in a real urban scenario is evaluated against the measurements presented in Part I (Fernández-Pampillón et al., 2020). Results show that the application of photocatalytic materials in an urban environment yield a minimal reduction in NO2 concentrations below 1 % under the studied atmospheric conditions. In a hypothetical scenario, in which the photoactive area is extended to an entire neighbourhood, small decrease of NO2 concentrations below 2 % is obtained under the daytime prevailing atmospheric conditions of the area of interest. Finally, the reduction of NO2 under several atmospheric conditions results to be mainly dominated by wind flow and NO x emissions in the study street. Highlights: Application of photocatalytic paints in urban areas to reduce NO2 is investigated NO2 mitigation is well modelled through the deposition velocity and NOx-O3 chemistry Minimal reduction of NO2 up to 1% is reached in the real urban scenario Lower wind speeds increase the NO2 reduction at pedestrian level Mitigation of on-road NO2 becomes less relevant in high-pollution sites